A fenomenologia de ser professora em uma classe hospitalar - Bragio, Jaqueline (2019)
This study aimed to comprehensively describe “what is” and “how is” the phenomenon: being a special education teacher in a hospital class. As a theoretical framework we intentionally chose Carl Ransom Rogers and Viktor Emil Frankl, working on two specific themes, markedly subjective themes, which were: "experience" ("experiencing") and "will to meaning". Methodological trajectory was: phenomenological research developed in a hospital class of a public children's hospital. Participants were two teachers who work in this class. Data production was performed on different days, during my stay at the teachers working place hours. There was no pre-established time limit and participants told about their free life. In accordance with phenomenological research method, a triggering question was launched in order to meet proposed research objective: “What is” and “How is it” to be a Special Education teacher involved in the “existential daily life” of the hospital class? We used researcher's field diary, which served for description (movement of research involvement) and reflection (reflective distancing). As a procedure and data analysis we adopted the phenomenological attitude, working with the Sense Guide tool, which has the phenomenological-existential psychology. The unveiling of phenomenon has shown us that life is guiding teachers, whether they are immersed in or involved in "inter-human experience" (Rogers) and from this place-time the "will to meaning" emerges or is born with power (Frankl). In life itself exists joy, which by the data indicates the greatest power and strength, and sadness, in a much smaller presence, associated with pain and death, which are still overcome, making the "tendency to update" (Rogers) and to the "meaning of life" (Frankl). On each side of life, which is really only one (side), we find two general Sense Guides, or to put it in another way, the background texture that existentially structures all other sense guides perceived as figures (from one background). We seek to capture (like fish) and capture (as meaning) their defense impulses and shields: they resort to "ways of being" in their "being in the world" through BE-KNOWLEDGE and BE-OUTRIGHT. Life never ends, it ceases for organisms, it goes on, there are ways out, and there is always an invitation for more life.